Cap polyposis in children: case report and literature review - Brunner, Maximilian; Agaimy, Abbas; Atreya, Raja; Grützmann, Robert; Matzel, Klaus E. (International Journal of Colorectal Disease, 2019)
PURPOSE: Cap polyposis is a benign disease of the colon, characterized by inflammatory polyps with a "cap" of inflammatory granulation tissue. Its prevalence is very low, especially in children. METHODS AND RESULTS: A 16-year-old girl presented with frequent bowel movements with mucous discharge and bloody stool, leading to the initial suspicion of chronic inflammatory bowel disease. Results of further investigation by endoscopy and histological examination were consistent with a diagnosis of cap polyposis. Treatment with systemic steroids resulted in symptom improvement. CONCLUSION: A review of the literature shows that cap polyposis can occur at any age, including childhood, with a slight predilection for the male gender. Rectal bleeding and rectal polyps are consistent features in all reported cases. Other typical symptoms include constipation, diarrhea, and abdominal pain. Symptoms may be very similar to those of chronic inflammatory bowel disease, the most important differential diagnosis. The cause of cap polyposis is still unclear, and specific therapy has not as yet been established. Conservative therapeutic measures should be preferred, especially in children.
EVALuna2:52991